Clinical presentation of Oropouche virus infection: A systematic review and meta-analysis. - Zhilin Wang; Linzhu Huang; Xinyu Zhang; Xinyue Zhang; Liwei Huang; Xiaoying Zhu; Xidai Long; Demin Cao; Yulei Li (PLoS Neglected Tropical Diseases)
Background The recent surge in incidence and geographic spread of OROV infections poses an escalating threat to global public health. However, studies exploring the clinical signs of OROV infection remains exceedingly limited. Methods We searched for OROV studies published until June 17, 2024, in several electronic databases including MEDLINE, EMBASE, SCOPUS, and the Cochrane Library. Results In total, 15 studies involving 806 patients with OROV infection were eligible for inclusion. General symptoms with fever and headache were the most common. Gastrointestinal disturbances like nausea/vomiting, anorexia, and odynophagia were also prevalent, along with ocular symptoms, mainly retro-orbital pain, photophobia, and redness. Respiratory symptoms, such as cough, sore throat and nasal congestion, are present, and skin-related issues like rash, pruritus, and pallor were also identified. Conclusion Overall, this study provides a foundational understanding of OROV's clinical manifestations to guide diagnosis, management, and public health interventions against this neglected tropical disease.